Answer:
![x = - 3](https://tex.z-dn.net/?f=x%20%3D%20%20-%203)
![y = - 2](https://tex.z-dn.net/?f=y%20%3D%20%20-%202)
Step-by-step explanation:
Since y=x+1 plug it into bottom equation as y.
![x + 1= 5x + 13](https://tex.z-dn.net/?f=x%20%2B%201%3D%205x%20%2B%2013)
Subtract 1 from both sides
![x = 5x + 12](https://tex.z-dn.net/?f=x%20%3D%205x%20%2B%2012)
Subtract 5x from both sides
![- 4x = 12](https://tex.z-dn.net/?f=%20-%204x%20%3D%2012)
Divide both sides by -4
![x = - 3](https://tex.z-dn.net/?f=x%20%3D%20%20-%203)
Now x=-3 into the top equation to find y
![- 3 + 1 = - 2](https://tex.z-dn.net/?f=%20-%203%20%2B%201%20%3D%20%20-%202)
y=-2
Answer:
76/100 or simplified into 19/25
Answer:
Y=6
X=0
Step-by-step explanation:
Hope this helps
Answer:
x= 70°
Step-by-step explanation:
the lines overlapping the two sides on the triangle mean that those two sides are congruent, meaning that both of those angles would be equal to 70°
Answer:
17. m=-1/2
18. m=-1
Step-by-step explanation: